2014
DOI: 10.1001/jamasurg.2013.3037
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Therapy for Triple-Negative Breast Cancer

Abstract: Breast-conserving therapy for TNBC is not associated with increased LR compared with non-TNBC subtypes. However, the TNBC phenotype correlates with worse overall survival. Breast-conserving therapy is appropriate for patients with TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
1
44
1
1
Order By: Relevance
“…Haffty et al 33 as well as Freedman et al 34 also found no significant differences in IBTR among patients treated with BCT when comparing TNBC with non-TNBC. A recent study by Gangi et al 35 examined outcome among 1,851 consecutive patients treated between 2000 and 2012, during which trastuzumab was routinely used for HER2-positive patients. There was no significant difference in IBTR among patients with TNBC compared with other subtypes of tumors.…”
Section: Median Year Of Recruitmentmentioning
confidence: 99%
“…Haffty et al 33 as well as Freedman et al 34 also found no significant differences in IBTR among patients treated with BCT when comparing TNBC with non-TNBC. A recent study by Gangi et al 35 examined outcome among 1,851 consecutive patients treated between 2000 and 2012, during which trastuzumab was routinely used for HER2-positive patients. There was no significant difference in IBTR among patients with TNBC compared with other subtypes of tumors.…”
Section: Median Year Of Recruitmentmentioning
confidence: 99%
“…In total, 1,182 titles were reviewed, 5 studies [14,15,18,19,20] including 2,922 non-TNBC and 510 TNBC cases were selected. The characteristics of included studies are summarized in supplemental table 1 A-C (www.karger.com/?DOI=441436) .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 3 studies did not define clear cutoffs for positivity of ER and PR. HER2 status was obtained through IHC in 2 studies [14,18], and IHC/fluorescent in situ hybridization (FISH) in 3 studies [15,19,20]. During the study period of Solin et al [14], the currently accepted system of scoring HER2 expression as 0, 1+, 2+, or 3+ was not generally used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, patients with TNBCs do not benefit from commonly used antiestrogen and herceptin-based therapies (4,5). Although chemotherapy is currently the mainstay of systemic treatment for breast cancer, patients with TNBC disease have a worse outcome after chemotherapy than patients with other subtypes of breast cancer (6,7). Previous studies revealed that neoadjuvant treatment involving the administration of chemotherapy before surgery was effective in a minority of women with TNBCs who showed a complete pathologic response and an excellent outcome; however, a relatively poor outcome was observed for the majority of the population with residual disease after treatment.…”
Section: Introductionmentioning
confidence: 99%